Impact of 3 months of detraining after high intensity exercise on menopause-related symptoms in early postmenopausal women – results of the randomized controlled actlife project - Jungmann, Sophia; Hettchen, Michael; Kohl, Matthias; Kemmler, Wolfgang (Frontiers in Sports and Active Living, 2023)
Regular exercise might reduce postmenopausal symptoms, however even short-moderate periods of absence from exercise training might significantly reduce these positive effects. The aim of the study was thus to determine detraining effects on postmenopausal symptoms after a 3-month detraining period in early post-menopausal women. After 13 months, the exercise group (EG: n = 27; 54.6 ± 2.0; 23.6 ± 3.3 kg/m2) had to abruptly stop their supervised, facility-based, high intensity aerobic and resistance group exercise conducted three times per week due to the COVID-19 pandemic and the corresponding lockdown of all training facilities in Germany. In parallel, the control group (CG: n = 27; 55.6 ± 1.6 years, 25.2 ± 5.2 kg/m2) had to terminate their low-intensity exercise program performed once per week. Study endpoint as determined after 3 months of detraining was menopausal symptoms as determined by the Menopausal Rating Scale II (MRS II). The intention to treat principle with multiple imputation was applied. After 13 months of intense multicomponent exercise and significant exercise-induced effects on menopausal symptoms, a further 3 months of detraining resulted in non-significant deteriorations (p = .106) in the exercise group, while non-significant improvements were observed in the control group (p = .180). Corresponding group differences were significant (p = .036) after detraining. Of importance, self-reported individual outdoor activities increased by about 40% in both groups during the three-month lock-down period. Three months of absence from a supervised high-intensity group exercise protocol resulted in detraining effects on postmenopausal symptoms even when outdoor physical activity was increased significantly. Trial registration number ClinicalTrials.gov: NCT03959995